PENGARUH PENGENDALIAN INTERNAL T PENGARUH PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN KECURANGAN (FRAUD)(Studi Kasus di Baitul Maal Wan Tamwil Nahdlatul Ulama Jombang) - nurul huda; Meta Ardiana (JURNAL AKUNTANSI, 2021)
This research aims for knows five indicator of intern control that is: prevention fraud (case study in BMT NU Jombang). Type research used in this research is quantitative. This research use analysis file quantitative technic with collection file survey technic (observation) use premary to get from population. Sample in this research is 43 respondent. Sample take nonproblably sapling technic take of sample from element population selected for basic volunteer or respondent can represent population and selection become sample. File analysis technic using multiple liniar regression. The research of study show that: (1) control environment don’t affect fraud preventionin BMT NU Jombang. (2) risk value affect fraud prevention in BMT NU Jombang. (3) control activities affect fraud prevention in BMT NU Jombang. (4) communication and information don’t affect fraud prevention in BMT NU Jombang. (5) supervision or monitoring don’t affect fraud prevention in BMT NU Jombang.